Some aspects of modernization of the far east (japanese) sociality: experience for Ukraine - Мозгова, Т. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
This article analyzes the new geopolitical challenges facing modern Ukraine, which today is an important strategic partner between Eastand West. The future of Ukraine – is the prospect of transregional cooperation with countries of the Far East.